Tolerance Evaluation Using Different Methods Against Soybean Rust caused by Phakopsora pachyrhizi - BAISWAR, P.; TIAMEREN AO, N.; UPADHYAY, D. N.; CHANDRA, S. (Indian Journal of Hill Farming, 2014)
Eight varieties viz. NRC 80, DS 2613, MACS 1140, MAUS 417, AMS 1, MACS 1184, JS 335 and MACS 1039 of soybean were screened for tolerance against rust using different methods. Variety NRC 80 was found to be the best according to WiPi rankings followed by DS 2613 and MACS 1140. Our results show that the use of different measures like Piu, Wiu and WiPi, both individually and in combination for identification of tolerant varieties, lines are better than the max-min method.